COMPARING PATHWAYS AND OUTCOME FOR PATANI MUSLIM WOMEN OF DIFFERENT EDUCATION SYSTEMS SINCE 1959 - Taweeluck Pollachom (Islam Realitas: Journal of Islamic and Social Studies, 2015)
A new era of resolving the conflicts in the three southern border provinces of  Thailand began in the time of Field Marshal Sarit Thanarat  (1959-1963), with an assimilationist policy toward the Malay Muslims of the three southern  provinces. This involved not only assimilation through  educational, economic, and social development policies but also assimilation of the Malay Muslims in the southern border provinces with the Muslims of the central areas of Thailand through variou sgovernment  projects, such as the dhammacharika project. These projects initially began with an emphasis on the religious leaders of the communities, on bringing Muslim students on field trips to Bangkok, and on providing  instruction  and training  for  Muslim  women. All of these projects received support  from various Muslim associations and organizations in central Thailand. Eventhough this assimilationist  policy might be viewed as destroying the religious and cultural identity of Malay-Muslims in Yala, Pattani, and Narathiwat provinces. The field research data show that not only their education routes correlate with differences of status, family background, class, and degree of austerity inreligious practice, but the differences among the Muslim countries where they studied also have important  effects on their identity formation  and consequent  Malay-Muslim  consciousness. All of these differences  also had significant effects on their social roles and statuses after returning to work in their hometown  areas, and have also had important  effects on the ways in which Muslim women of this area display their piety.  Era baru menyelesaikan konflik etnik Thailand di tiga provinsi perbatasan selatan telah dimulai pada saat Field Marshal Sarit Thanarat (1959-1963), dengan kebijakan asimilasi terhadap Muslim Melayu. Hal ini tidak hanya melibatkan asimilasi melalui kebijakan pendidikan, ekonomi, dan sosial tetapi juga asimilasi Muslim Mayu dengan Muslim dari daerah Thai pusat melalui berbagai proyek pemerintah, seperti proyek dhammacharika. Proyek-proyek ini awalnya dimulai dengan penekanan pada para pemimpin agama dari masyarakat, untuk membawa siswa Muslim dengan kunjungan lapangan ke Bangkok, dan pelatihan bagi perempuan Muslim. Semua proyek ini mendapat dukungan dari berbagai asosiasi dan organisasi Muslim di Thailand pusat. Meskipun kebijakan asimilasi ini mungkin dipandang merusak identitas agama dan budaya Melayu-Muslim di Yala, Pattani, dan Provinsi Narathiwat. Data penelitian lapangan menunjukkan bahwa mereka mampu berkorelasi dengan perbedaan status, latar belakang keluarga, kelas, tetapi juga memiliki efek penting pada pembentukan identitas dan kesadaran Melayu-Muslim. Semua perbedaan memiliki efek yang signifikan terhadap peran setelah kembali bekerja di kampung halaman, dan juga memiliki efek penting wanita Muslim untuk menampilkan kesalehan mereka.